Deciphering Discursive Practices in Imran Khan’s Discourse on Islamophobia in OIC 48th Session: A Faircloughian Study - Abrar, Muhammad; Saleem, Shakira; Khan, Sheeza Altaf Hussain (Annals of Human and Social Sciences, 2024)
This study aimed to critically examine the linguistic arguments, discursive and sociocultural practices in the political speech of the former Prime Minister, Imran Khan that was delivered in 48th session of the OIC council of foreign ministers held in Islamabad. Islamophobia as a sensitive matter that requires immediate resolution, was primarily discussed in the speech. The study adopted a qualitative approach and employed Fairclough’s (1989) Three-Dimension (3D) model for analysis, consisting of descriptive (textual), interpretive (contextual) and explanation (sociocultural) domains. The findings revealed that the former PM delivered his speech with strategic consideration of various linguistic features to address the issue. His chosen language was influenced by socio-political context. The explanation level demonstrated that the carefully crafted language majorly contributed to impart his ideology that Islam is the religion of peace. Furthermore, this study suggested that Islam's image and reputation as a religion of peace in the international community can be improved by discussing Islamophobia at international forums using strategic linguistic resources.